Venture Capital as an Alternative Capital for Vezara MSMe in PGC East Jakarta - Yusbardini, Yusbardini (CV. Proaksara Global Transeduka, 2024)
Venture capital is a financing business in the form of capital participation in a company that receives financing assistance for a certain period of time. Venture capital, which is a form of financing institution, can be an alternative and active investment for MSMEs in Indonesia by participating in providing business capital and followed by the involvement of venture capital companies in the management of MSMEs. The purpose of this service is to provide Venture capital counseling as an alternative capital for MSMEs. The weaknesses faced by MSME entrepreneurs in improving business capabilities are very complex and include various indicators, one of which is the problem of capital. Therefore, the PKM Untar team tried to provide counselling on venture capital as an alternative capital for MSMEs. Venture capital counselling is conducted online using zoommetting. The result of this PKM activity is that partners understand venture capital as an alternative to financing MSME businesses.